A path towards a better characterisation of silicon thin‐film solar cells: depth profile analysis by pulsed radiofrequency glow discharge optical emission spectrometry. (12th June 2013) - Sanchez, Pascal; Fernández, Beatriz; Menéndez, Armando; Gómez, David; Pereiro, Rosario; Sanz‐Medel, Alfredo
ABSTRACT The analytical potential of radiofrequency pulsed glow discharge optical emission spectrometry (rf‐PGD‐OES) is investigated for quantitative depth profiling analysis of thin‐film solar cells (TFSC) based on hydrogenated amorphous silicon (a‐Si:H). This method does not require sampling at ultra‐high‐vacuum conditions, and so it facilitates higher sample throughput than do reference techniques. In this paper, the determination of compositional depth profiles of a‐Si:H TFSC was performed by resorting to a multi‐matrix calibration procedure. For this purpose, certified reference materials, as well as laboratory standards based on individual layers of doped a‐Si:H, were simultaneously employed to build the analytical calibration curves. Results show that rf‐PGD‐OES allows us to discriminate the different layers of photovoltaic devices: the front contact composed by ZnO:Al2O3 (AZO), the a‐Si:H layer (the B‐doped, intrinsic a‐Si:H and P‐doped films), the AZO/Al back contact and substrate. A good agreement with the nominal values for element concentrations (e.g. 0.4% of H, 1.5% of B and 3.7% of P) and layer thicknesses (in the range of 950 nm for the front contact and 13 nm for the P‐doped a‐Si:H layer) was obtained, demonstrating the ability of rf‐PGD‐OES for a direct, sensitive and high‐depth‐resolution analysis of photovoltaic devices. Moreover, diffusion processes between the coating layers, which could have an important influence on the final efficiency of TFSC, can be identified as well. Hence, the findings support the use of rf‐PGD‐OES as an analysis method in the development of photovoltaic thin films. Copyright © 2013 John Wiley & Sons, Ltd.